Analisis Dampak Lalu Lintas Pembangunan Pabrik Kelapa Sawit PT Palma Bumi Lestari: Abstract, introduction, research methods, results and discussion, conclusion, references. - Sugasta, Hervian Handika; Santosa, Dimas Puji; Saputra, Doddy Cahyadi; Adibah, Fairuz (Jurnal Teknologi Infrastruktur, 2024)
Indonesia is the world's largest producer of palm oil, with a production of 36 million tons in 2019. The construction of palm oil mills is expected to have an impact on the environment and traffic, including public attitudes, traffic flow, congestion, and safety. According to Minister of Transportation Regulation No. 17 of 2021, a traffic impact analysis is mandatory for developments that have the potential to cause disruptions, in order to assess the impact of palm oil mill construction. This study examines the impact of palm oil mill construction on traffic, particularly the influence of the Degree of Saturation (DS) and Level of Service (LOS). The research methodology includes data collection, road performance analysis using the 1997 Indonesian Highway Capacity Manual (MKJI), and micro-traffic simulation to evaluate road network performance and the transportation system. This study also employs four stages of traffic modeling as an analytical method. The analysis results indicate that in zones with the Do-Something scenario based on approach type and cycle time, the Degree of Saturation (DS) decreases annually, while the Level of Service (LOS) remains unchanged. Meanwhile, in zones with the Do-Something scenario based on geometric improvements, significant improvements are observed, with an increase of 29.3% on Jalan Raya Pulau Bendu and 13.8% on Jalan Raya Ngabang – Sanggau. However, the Level of Service (LOS) remains unchanged..